Electrical Energy Audit: Electrical Energy Audit at Block QB Faculty of Electrical and Electronic Engineering Universiti Tun Hussein Onn Malaysia - Ahmad Shukor, Abdul Razak; Mohd Yousof, Mohd Fairouz (Evolution in Electrical and Electronic Engineering, 2023)
As the demand for energy continues to rise, organizations and individuals are increasingly realizing the importance of optimizing energy consumption to reduce costs, enhance operational efficiency, and minimize environmental impact. Several researchers who have done electrical energy audit on the designed location or building play crucial role in identifying potential areas of improvement and developing strategies for effective power management. This research is done for block QB University Tun Hussein Onn Malaysia in order to achieve effective power consumption or management. Three test is conducted by using different equipment which lux meter is for illuminance test, temperature and humidity data logger to record both the temperature and humidity in the area and lastly thermal imager camera to detect any problem related to air insulation in a specified room. These data were analyzed and energy saving measure (ESM) were proposed. Benefits derived from electrical energy audits, including cost savings, enhanced energy efficiency, and compliance with energy regulations. By identifying energy wastage and implementing appropriate measures, responsible electrical organization for block QB can achieve substantial energy savings, cost reduction and contribute to a more sustainable future.